Relationship Between Parenting Styles and Students’ Adaptability to Blended Learning Environments in Uyo Metropolis of Akwa-Ibom State Nigeria - Menyene-AbasiAndem Udo; Iniabasi Faith Imafidon; Habiba Anazou Abdulkadir (IJOEM: Indonesian Journal of E-learning and Multimedia, 2025)
This study examined the relationship between Authoritative, authoritarian, permissive and uninvolved parenting styles and students’ adaptability to blended learning environments in Uyo Metropolis of Akwa-Ibom state, Nigeria. The study sample consisted of 361 students. The study employed a correlational design. The instruments used for data collection were the parenting styles questionnaire and the students’ adaptability to blended learning environments questionnaire. Data were analyzed using descriptive and inferential statistics. The descriptive statistics were used to analyze the Bio-data of the respondent; while the inferential statistics of Pearson Product Moment Correlation (r) were used to test all four hypotheses at 0.05 alpha level of significance. Findings revealed a significant positive relationship between Authoritative Parenting and students’ adaptability to blended learning environments (r=0.714, p=0.001). There is a significant negative significant relationship that exists between authoritarian parenting style and students’ adaptability to blended learning environments (r= -0.625, p= 0.002). There is a strong negative significant relationship that exists between permissive parenting style and students’ adaptability to blended learning environments (r=0.792, p= 0.010). That there is a strong negative significant relationship that exists between uninvolved parenting style and students’ adaptability to blended learning environments (r=0.792, p= 0.010). Based on the findings, it was recommended that educational psychologists and school counselors should educate parents on the benefits of an authoritative parenting style, through Workshops and resources that will help parents create supportive environments that encourage independence and adaptability in their children.